Exploring the Integration of Atomic Habits in Pedagogical Frameworks: A Qualitative Analysis of Teachers’ Implementation and Students’ Outcomes - Ul-Zaman, Fakhar; Bhatti, Muhammad Safdar; Semab, Samina; Aslam, Muhammad Junaid; Anwer, Muhammad Awais; Noor, Maria (Universitas Andalas, 2025)
The purpose of this study was to explore the incorporation of the tenets of Atomic Habits in pedagogical practice and to examine how teachers employ habit-based techniques to influence student learning. As the education system more and more encourages this approach to improving engagement and academic success, it becomes critically important to understand how small, consistent changes in behavior can impact learning. The aim of this study is to demonstrate how Atomic Habits by James Clear, a bestseller that details the laws of habit, can be applied to teaching and how this application may benefit student motivation, behavior, and outcomes. A qualitative methodology was employed, which consisted of 15 personal interviews with teachers from secondary schools. The teachers, from schools in Narowal, Pakistan, were purposively chosen. The analysis also included content analysis of the book Atomic Habits as well as related academic literature to analyze whether reported habit formation strategies offered a potential reality check and correlation with student success. Interview data were thematically analyzed to determine key learning regarding the application and impacts of habit-based strategies. The results indicate that when teachers employed strategies like identity-based habits, habit stacking, and environmental structuring, they experienced an enhancement in the students’ motivation, academic engagement, and performance. However, some limitations were identified, including the ability to maintain a common approach across a range of student interests and class sizes. This study adds to our knowledge of how small-scale, incremental changes in students' behavior will, through habit-building interventions, have the potential to greatly improve educational performance. The findings of the study imply that habit-based teaching methods may have a tremendous impact on student performance. Subsequent research could investigate the longer-term effects of habit creation on students' outcomes and examine the role that technology can play when used to support habit formation within an educational setting.